Time-resolved compositional and dynamics analysis of biofilm maturation and dispersal via solid-state NMR spectroscopy - Yi Xue; Xue Kang (npj Biofilms and Microbiomes)
Abstract Dispersal plays a crucial role in the development and ecology of biofilms. While extensive studies focused on elucidating the molecular mechanisms governing this process, few have characterized the associated temporal changes in composition and structure. Here, we employed solid-state nuclear magnetic resonance (NMR) techniques to achieve time-resolved characterization of Bacillus subtilis biofilms over a 5-day period. The mature biofilm, established within 48 h, undergoes significant degradation in following 72 h. The steepest decline of proteins precedes that of exopolysaccharides, likely reflecting their distinct spatial distribution. Exopolysaccharide sugar units display clustered temporal patterns, suggesting the presence of distinct polysaccharide types. A sharp rise in aliphatic carbon signals on day 4 probably corresponds to a surge in biosurfactant production. Different dynamic regimes respond differently to dispersal: the mobile domain exhibits increased rigidity, while the rigid domain remains stable. These findings provide novel insights and perspectives on the complex process of biofilm dispersal.